Your second step is wrong
(2x-5)-(x) = 8.6 - (2x-5)
x-5 = 8.6 - 2x +5 = 13.6 - 2x
3x = 18.6 OR x = 6.2
I am sure you would have got it
1. The first three terms of an arithmetic sequence are given by x, (2x-5), 8.6.
Determine the first term and the common difference.
I know that d = t2 - 1 = t3 - t2
So, (2x-5)-(x) = 8.6 - (2x-5) (Trying to solve for difference)
x - 5 = 3.6 - 2x
-5 = 3.6 - x
-5-3.6 = - x
x = 8.6
x = d
This is what I did and it was wrong... I'm not sure how to do this question. :/
The answer is t1 = 6.2 d = 1.2
Mathnood
Next time for such kind of exercises use the basic property of Arithmetic Progression wich simply states that if 3 numbers a,b,and c are consecutive terms of an A.P then the mid term b is the arithmetic mean of the two others i.e : b=1/2[a+c]
Minoas